Does religiosity matter for green hotel selection? An empirical investigation on Chinese religious consumers - Wang, L.; Wang, Z. X.; Zhang, Qi; Wong, P. P. W. * (TEMAPOR, 2021)
Previous investigation of green purchase attitude-behavior gap has shown inconclusive or even controversial results. Researchers appear to have under-estimated or ignored religiosity as an individual’s fundamental belief and core values that influence a consumer’s decision-making process. The purpose of this study is to examine the relationship between religiosity, consumers’ green purchase attitudinal characteristics, and behavioral aspects i.e., consumer attitudinal loyalty. A total of 418 usable questionnaires were collected to empirically test the hypotheses using SPSS and Structural Equation Modeling. The results showed that religiosity positively influenced perceived consumer effectiveness, environmental concern, environmental knowledge, and ultimately, leading to consumer loyalty. In addition, religiosity displays negative influence on consumer loyalty. This study expanded the existing knowledge based on green hotel selection among Chinese religious consumers in the tourism literature. The empirical findings would greatly benefit hotel managers and other key stakeholders in the hospitality industry.